EAACI Food Allergy and Anaphylaxis Guidelines. Primary prevention of food allergy. Issue 5 (3rd April 2014) - Muraro, A.; Halken, S.; Arshad, S. H.; Beyer, K.; Dubois, A. E. J.; Du Toit, G.; Eigenmann, P. A.; Grimshaw, K. E. C.; Hoest, A.; Lack, G.; O'Mahony, L.; Papadopoulos, N. G.; et al.
Abstract Food allergy can have significant effects on morbidity and quality of life and can be costly in terms of medical visits and treatments. There is therefore considerable interest in generating efficient approaches that may reduce the risk of developing food allergy. This guideline has been prepared by the European Academy of Allergy and Clinical Immunology's (EAACI) Taskforce on Prevention and is part of the EAACI Guidelines for Food Allergy and Anaphylaxis. It aims to provide evidence‐based recommendations for primary prevention of food allergy. A wide range of antenatal, perinatal, neonatal, and childhood strategies were identified and their effectiveness assessed and synthesized in a systematic review. Based on this evidence, families can be provided with evidence‐based advice about preventing food allergy, particularly for infants at high risk for development of allergic disease. The advice for all mothers includes a normal diet without restrictions during pregnancy and lactation. For all infants, exclusive breastfeeding is recommended for at least first 4–6 months of life. If breastfeeding is insufficient or not possible, infants at high‐risk can be recommended a hypoallergenic formula with a documented preventive effect for the first 4 months. There is no need to avoid introducing complementary foods beyond 4 months, and currently, the evidence does not justify recommendations about either withholding or encouraging exposure to potentially allergenic foods after 4 months once weaning has commenced, irrespective of atopic heredity. There is no evidence to support the use of prebiotics or probiotics for food allergy prevention.